Parental Engagement in Children's Education: A Key Factor in Academic Achievement and Learning Motivation - Owoyale-Abdulganiy, Ibrahim Solahudeen; Olokooba, Issa Nasiru (Mimbar Ilmu, 2024)
Many families still face various challenges in providing optimal academic support, such as time constraints, lack of knowledge, and financial issues. This study aims to analyze the impact of parental involvement on students' academic achievement and to identify strategies that can enhance parents' roles in supporting their children's education. The research employed a descriptive survey approach with a simple random sampling technique. Data were collected from three participants, consisting of elementary school students' guardians, through closed questionnaires and in-depth interviews. The collected data were analyzed using descriptive statistics to identify patterns of involvement and their impact on students' academic performance. The results showed that parental involvement significantly contributes to students' academic success. Parents who actively provide support, such as assisting with homework, providing adequate learning resources, and maintaining communication with the school, can enhance children's learning motivation. However, several obstacles were identified in this study, including parents' time limitations due to work commitments, a lack of understanding of the learning materials, and financial constraints in providing optimal learning facilities. This study concludes that increasing parental involvement is crucial in supporting children's educational success.